ESP Learning Context Through the Lens of Tertiary-Level Economics Students - Grubor, Jelena V.; Luković, Maja R. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
English for Specific Purposes (ESP) primarily focuses on learners’ current and future professional needs. The context in which English is learned is thus likely to play an important role in learners’ future professional contexts. The main objective of the study was to determine learners’ attitudes toward the L2 learning context (L2LC), while the subsidiary aim was to examine whether differences exist according to sex and language proficiency level. The sample included N = 125 Economics students in Kragujevac. The research was anonymous and participation was voluntary. The main research instrument used to determine participants’ attitudes was the Attitudes to L2 Learning Context scale (AL2LC), which showed good internal consistency (α = .859). The collected data were analysed using IBM SPSS Statistics 26. Overall, the results indicate that the sample reported mildly positive attitudes toward L2LC regardless of sex or language proficiency level, and that the individual L2LC aspects were evaluated positively. In order to gain deeper insights into the role of L2LC in ESP settings in the light of L2 acquisition, future research should examine the relationship between ESP students’ attitudes and other factors relevant to ESP learning. This is important not only for theoretical considerations but also for practical implications in ESP classes.
Keywords: ESP; English learning context; AL2LC scale; tertiary-level Economics students